A flexible route to bioactive 6-alkyl-α-pyrones. Issue 9 (1st March 2017) - Qu, Yang; Kraus, George A.
Graphical abstract: Highlights: Development of a common intermediate for the synthesis of three biologically active pyrones. One-pot double decarboalkoxylation of pyrone malonates. Reaction scope expanded to 3-chloroisocoumarine. Abstract: Both 6-chloro-α-pyrones and 3-chlorobenzopyran-1-ones react with malonates followed by a double decarboalkoxylation to give the corresponding alkyl and alkenyl products.